Sistem Informasi Persediaan Barang Pada PT. TGA Berbasis Website Menggunakan Framework Laravel - Marli'aini, Navika Tiamy; Anggoro, Dimas Aryo (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
PT. Tiara Giri Agrapana is a tourism organization. The problem is that the warehouse administrator checks goods manually, and makes data reports on incoming and outgoing goods, there are often differences in the amount of stock, and employees have difficulty finding stock. The research aims to make it easier for administrators to compile monthly and annual stock reports, arrange picking up goods, and pick up goods by employees more easily than previous methods. The waterfall method is carried out sequentially from requirements analysis, design, development, testing, and maintenance. The system is designed using PHP language, MySQL, and Laravel framework. The black-box testing method was used as unit testing, the system was tested using SUS from 20 respondents with a result of 92.25, including the usable category. It was concluded that users well received the system. This research is expected to produce an information system that can simplify the work of warehouse administrators in making monthly and annual reports on goods data, time efficiency for entering and storing goods data, and make it easier for employees to submit goods